Determinants of Profit Distribution Management of Sharia Commercial Banks in Indonesia for the Period 2018-2022 - Mega Parwati; Syahfitri Suryaningsi Welkom* (Riwayat: Educational Journal of History and Humanities, 2024)
This study aims to analyze the factors that affect the management of profit distribution in Sharia Commercial Banks (BUS) in Indonesia. The bound variable used in this study is profit distribution management. The independent variables used in this study include capital adequacy ratio (CAR), proportion of third-party funds (PDPK), and quality of productive assets. The population in this study is all BUS registered with Bank Indonesia in the 2018-2022 period. Using the purposive sampling technique, a research sample of nine banks was obtained. The analysis method used is panel data regression analysis. The results show that the variables CAR and PDPK have a negative and significant effect on profit distribution management. Meanwhile, the variable of productive asset quality has no effect on profit distribution management. The results of this study are expected to be considered by Islamic banks to improve financial performance, especially to increase profit sharing and liquidity capabilities.